H2S GAS REMOVAL BY BIOFILTER USING COMPOST AND ACTIVATED CARBON AS PACKING MATERIALS - Mohamad Yani Purwoko Ahnur Wahyuni (Jurnal Teknologi Industri Pertanian, 2009)
The removal characteristics of hydrogen sulfide (H2S) by organic (compost) and inorganic (granular activated carbon) carriers were studied at a laboratory scale. The compost, activated carbon and mix of them with the ratio of 1:1 were evaluated as packing materials of packed tower deodorization apparatus (biofilter) from the view points of biological removal characteristics of H2S and some physical properties. The removal rate of H2S by compost, activated carbon and mix of them (1:1) in non-biological treatment were 0.22, 0.37, and 0.88 g-S.kg-dr-material-1 respectively. However, the maximum removal rates of H2S by biological treatment were 11.85, 14.66, and 20.49 g-S. kg dry-material-1 respectively. The removal rate of H2S from all packing materials after inoculated with mixed culture of Thiobacillus sp. was increased due to biological oxidation by Thiobacillus sp. The mixed of compost and activated carbon showed the best result to remove H2S from contaminated air. Keywords : Biofilter, H2S, Thiobacillus sp., compost, activated carbon.